LLM for Retail Business (Optimizing Clothing Sales with AI) - Deepali Narwade; Aditya Kanhere; Sahil Mulla; Atish Sanap; Abhay Patil (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This research paper presents an end-to- end implementation of a chatbot system tailored for the retail industry, utilizing a large language model (LLM). The chatbot is designed to assist employees of retail stores, such as clothing outlets, by providing real-time access to critical business data, including inventory levels, sales metrics, and profit margins. The solution aims to streamline decision- making processes, enhance operational efficiency, and improve information accessibility by reducing dependency on manual data retrieval. This approach leverages advanced natural language processing to simplify the interface between business systems and employees, ensuring accurate and timely responses to queries.